Calix[4]pyrrole aluminate: a planar tetracoordinate aluminum(III) anion and its unusual lewis acidity - Ebner, Fabian; Wadepohl, Hubert; Greb, Lutz (Journal of the American Chemical Society, 2019)
Tetracoordinate aluminum(III) anions are generally tetrahedral and non-Lewis acidic. Herein, we describe the first planar tetracoordinate aluminum anion. The anion is isolated in its free form, representing a new “anti-van’t Hoff/Le Bel” case. Despite its negative charge, it remains Lewis acidic and permits the formation of various unique adducts, e.g., a dianionic p-block metal hydride. Turning an inert spectator anion into a Lewis acid by planarization verifies theoretical predictions made 40 years ago, ultimately connects “anti-van’t Hoff/Le Bel” structure with reactivity, and pushes